DEVELOPMENT OF BIOLOGY LEARNING TOOLS OF COOPERATIVE-BASED MODEL OF NHT TYPE WITH CTL APPROACH ON DIGESTIVE SYSTEM SUBJECT TO GRADE XI OF SENIOR HIGH SCHOOL - Sulaiman, Isnada (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
This study is research and development which focuses on the development of cooperative learning tools of Numbered Heads Together (NHT) type with contextual Teaching and Learning (CTL) approach. The model used is referred to 4D (defining, design, development and dissemination) by Thiagarajan (1974). The development process on the dfining and design stages produced prototype 1 (lesson plan, students book and workbook). The development on the development stage was a validation process which produced a valid prototype 2. On tryout phase, the tools produced practical and effective tools and optimize the existing tools, revision was conducted to produce prototype 3. The development in dessimination stage was a disseminating phase of existing tools. The result of the dissemination stage was the final prototype. The result reveals that NHT learning tools with CTL approach has met effective criteria with indicators (1) the result of learning has met the minimum completeness criteria 68, that the classical completeness is also achieved, (2) teacher and students activities are in the category of completely conducted, (3) teacher’s competence in managing the learning is in high category, and (4) students response has met the criteria and is in positive category. Based on the examination of the experts and the result of the test indicate that the cooperative learning tools of NHT type with CTL approach has met the criteria of validity, practical, and effective.